Solid Phase Sorption of Phenols on Metals Acetylacetonates; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Gavrilenko M. A. Mikhail Alekseevich (2014, 2014)
Title screen